Application of Process Mining in the Process of IT Incidents Management by Utilizing Kaggle’s Dataset - Anggraeni Xena Paradita; Fakhri Arya Fadhillah; Kanza Azzahra; Michael Christensen Bonar Kasparov; Rachmadita Andreswari (Faculty of Computer Science (FILKOM) Brawijaya University, 2023)
The application of process mining in Information Technology (IT) incident management has been carried out. In the face of the increasing complexity of IT systems and a surge of incidents, traditional incident management is no longer effective. This study uses Kaggle's dataset on IT incident management to analyze event logs, identify process bottlenecks, and compare process flows seen in event logs with expected flows. Process mining techniques, such as process discovery and conformance, are applied using PM4PY and Celonis tools. The analysis results with process mining produce a new model process that can be applied in practice with a conformance rate of 81%.